The Regulation of Defendant’s Religious Identity in Court Decisions - Nandang Sutrisno; Despan Heryansyah; Sahid Hadi; Christopher M. Cason (Administrative Law Departement Faculty of Law Universitas Sebelas Mare, 2022)
This study focuses on using religious attributes in the trial process of corruption cases in Indonesia, the judge’s consideration of the decency of a defendant, and the regulation of a defendant’s religious identity in the court decision. By identifying the judge’s perspective on a defendant's religious attributes and aspects of decency as an interpretative scheme and constructing their significance on it, this study also presents an analysis of the application of the principle of impartiality of judges and courts based on the Bangalore Principles. Impartiality itself is positioned as the bedrock of judicial integrity. With a field-based research method, this study reveals that religious identity has influenced judges and court decisions, especially considering mitigating factors in criminal sentencing. These findings indicate that the Bangalore Principles fall short of clear guidelines to counter such bias and a clear framework in Indonesia’s judiciary to restore its integrity.